Human Resource Artificial Intelligence Implementation and Organizational Performance in Malaysia - Xin, Ooi Kai (Animo Repository, 2022)
The purpose of this study is to examine the effects of perception on human resource (HR) artificial intelligence (AI) implementation on organizational performance in Malaysia. There are three dimensions of perception of HR AI implementation, namely, talent acquisition process, human capital development process, and performance management process. Data were collected online from 352 respondents with HR backgrounds in Malaysia and analyzed using partial least square structural equation modeling (SmartPLS). The results indicated that AI implementation in the talent acquisition process, human capital development process, and performance management process has a significant positive effect on organizational performance in Malaysia. This study makes a significant contribution to the HRM process literature by examining the effects of HR AI implementation on organizational performance. It provides vital insights to business organizations to consider implementing AI in their Human Resource Management (HRM) processes for a successful business. Studies that have investigated HRM functions and been published are rarely based on countries like Malaysia. Therefore, this study corroborates the assertion to conduct more empirical studies on the adoption of AI in HRM processes and its potential influences on organizational performance in Malaysia.